509,773 views
2 votes
2 votes
Given: F(x) = 2x and G(x) = x2+ 2 Find (G - F)(x).

User Daniel Corzo
by
2.8k points

1 Answer

7 votes
7 votes

Answer:

(F+G)(x)= x²+2x+2

Explanation:

Finding the answer is pretty simply:

The given equations are

F(x) = 2x

G(x) = x²+2

Finding (F+G)(x).

Now we simply have to add the values of both functions F(x) and G(x).

(F+G)(x) = F(x) + G(x)

All we have to do is substitute the values of both functions F(x) and G(x) into the given equation.

(F+G)(x) = (2x) + (x² +2)

Rearranging the terms

(F+G)(x)= x²+2x+2

P.S. thanks to AmeerAbdullah for the awesome answer.

User Nawrez
by
2.5k points